Neural network based ATM admission controller - Joice Yanto (2008)
Broadband Integrated Service Digital Networks (B-ISDN), along with Asynchronous Transfer Mode (ATM), are designed to support the requirements of modern communication that cover multiple users with multimedia traffic including voice, data, video. The resource allocation by the ATM Connection Admission Control (CAC) is one of the crucial factors needed to meet the certain criteria of the network performance that must guarantee the quality of service negotiated of the existing connection. To develop a reliable ATM Connection Admission Controller is a very difficult task, because of the dynamic nature of the source traffic. The associated mathematical algorithm is complex.